Ritual Sesajen pada Pelaksaan Upacara Pernikahan Adat Jawa - Septia, Reni (Yayasan Alpatih Harapan Semesta, 2024)
Marriage in Javanese society is not only a legal and religious bond, but also involves a series of traditional processions that have spiritual and symbolic values. One important element in this procession is the offering, which is used to ask for blessings from ancestors and ask for blessings from God so that the marriage runs smoothly and is full of blessings. This article discusses the meaning and philosophy of the offering culture in Javanese traditional wedding rituals, especially in Grenjeng Village. This study uses a descriptive qualitative approach with interviews, observations, and documentation studies as data collection methods. Offerings in Javanese traditional weddings in Grenjeng Village contain various symbols that reflect life values, such as happiness, loyalty, and courage. Several elements in the offering, such as plantain, coconut, setaman flowers, kampung chicken eggs, shallots and garlic, chilies, rice, and mendong mats, each have a deep philosophy related to the hope that the bride and groom can live a harmonious and blessed household life. This study shows that the offering culture not only has a symbolic dimension but also functions as a medium for preserving local wisdom and spirituality in Javanese society. Therefore, it is important to preserve this tradition so that it remains relevant among the younger generation.